WOUND HEALING EFFICACY OF MOIST EXPOSED BURN OINTMENT (MEBO) AND SILVER SULFADIAZINE IN PARTIAL-THICKNESS BURNS: A SYSTEMATIC REVIEW - Wardhana, Aditya; Farhana, Nadya (Jurnal Rekonstruksi dan Estetik, 2025)
Highlights: Superior efficacy between MEBO and SSD in burn patients. Improved Clinical Outcomes of wound healing in burn patients. Natural, Plant-Based Alternative for burn patients.  Abstract: Introduction: Burn injuries are a common global health issue that often require prolonged wound care and can lead to complications such as infections, delayed healing, and surgical interventions. Silver sulfadiazine (SSD) has long been the standard topical treatment for partial-thickness burns, but concerns remain regarding delayed healing and potential side effects. Moist Exposed Burn Ointment (MEBO), a Chinese herbal-based topical agent containing sesame oil, beta-sitosterol, and berberine, has emerged as a potential alternative due to its anti-inflammatory, antimicrobial, and moisture-retaining properties. Method: This systematic review aimed to evaluate the efficacy of MEBO compared to SSD in partial-thickness burn wound healing. A comprehensive search of PubMed, Cochrane, and Science Direct using the terms “MEBO,” “SSD,” “Burns,” and “Wound healing” identified five trials conducted between 2000 and 2008. Result: The results consistently demonstrated that MEBO provided comparable or superior outcomes to SSD, including shorter wound healing time, reduced pain, absence of infection in wound swabs, minimal slough and crust formation, lower complication rates, and reduced need for surgical intervention. Conclusion: These findings suggest that MEBO is an effective and potentially preferable alternative to SSD for managing partial-thickness burn wounds.